Hubungan Kadar Timbal Dalam Darah dengan Tekanan Darah pada Pekerja Bengkel Kendaraan di Kecamatan Tampaksiring, Kabupaten Gianyar Tahun 2019: The Correlation of Blood Lead Levels and Blood Pressure in Vehicle Repair Shop Workers in Tampaksiring District, Gianyar Regency, 2019 - dwi putri, ni luh nova dilisca; Idayani, Sri (Stikes Wira Medika Bali, 2021)
Pollutant metals from vehicles with leaded gasoline can accumulate in the body, attack important organs, and even damage the quality of offspring. Lead poisoning (Pb) can be experienced by workshop workers through vehicle fumes that are being repaired. Chronic lead poisoning (Pb) most often is weakness, anorexia, miscarriage, tremors, weight loss, headaches and digestive tract symptoms. Lead entering the bloodstream can cause hypertension, this is because lead can lead to increased production of reactive oxygen species (ROS). This study aims to determine the relationship between the content of lead levels in blood with the occurrence of hypertension in workshop workers. Examination of blood lead levels is carried out using MPAES tools and blood pressure checks are carried out using digital tensimeter devices. The results showed that there was a correlation between blood lead levels and blood pressure in workshop workers in Gianyar Regency in 2019 with the bivariate Pearson correlation test producing sig. (2-tailed) of 0.008 <0.05 showed a correlation between variable levels of lead in blood with blood pressure (hypertension).